Is there an optimal respiratory reference position for self-navigated whole-heart coronary MR angiography? - Piccini, Davide; Bonanno, Gabriele; Ginami, Giulia; Littmann, Arne; Zenge, Michael O.; Stuber, Matthias (Journal of magnetic resonance imaging, 2016)
Purpose To test the direct influence of the reference respiratory position on image quality for self‐navigated whole‐heart coronary MRI. Methods Self‐navigated whole‐heart coronary MRI was performed in 11 healthy adult subjects. Respiratory motion was compensated for by using three different respiratory reference positions of the heart: end‐inspiratory, end‐expiratory, and the mean of the entire respiratory excursion. All datasets were reconstructed without motion compensation for comparison. Image quality was assessed in all reconstructions using signal‐to‐noise ratio (SNR) and contrst‐to‐noise ratio (CNR) measurements, as well as percentage vessel sharpness and visible length of the coronary arteries. Results While SNR and CNR remained close to constant in all reconstructions, a clear and significant improvement in vessel sharpness was identified in all motion corrected datasets with respect to their uncorrected counterpart (e.g., percentage sharpness of the proximal right coronary artery (RCA): 61.6 ± 8.2% for end‐inspiration, 64.1 ± 10.7% for end‐expiration, and 63.3 ± 7.0% for the mean respiratory position versus 55.0 ± 10.4 for the uncorrected datasets; P < 0.05). Among all motion corrected reconstructions, the use of an end‐expiratory reference position most consistently provided the highest image quality. In particular, some of the improvements in vessel sharpness and length measured for end‐expiration were statistically significant with respect to the reconstructions performed at end‐inspiration (e.g., percentage sharpness of the proximal left anterior descending coronary: 58.2 ± 7.4% versus 55.8 ± 8.4%; P < 0.05; and visible length of the RCA: 125.7 ± 25.9 mm versus 114.4 ± 27.4 mm; P < 0.05). Conclusion The use of end‐expiration as a reference position for respiratory motion correction in free‐breathing self‐navigated whole heart coronary MRA significantly improves image quality. J. Magn. Reson. Imaging 2016;43:426–433.